Colombian Emigration by Administrative Regions - Mariana Saenz; Joshua J. Lewer (Institute for the Study of Labor (IZA), 2015)
This article contributes to immigration literature by applying a Random Utility Maximization model to derive a migration gravity model that explains factors affecting migration outflows per administrative unit and region for the country of Colombia. Negative binomial cross-sectional estimates indicate that departments sharing an international border and overall labor market conditions are significance determinants of migration patterns for the departments, but non-economic factors such as credit constraints and cultural networks also affect migration outflows. Estimation of regional migration outflows are also provided and yield unique findings per geographic location.
Keywords: F22; C25; H11; 330; emigration; Colombia; gravity model; negative binomial regression